Analysis Of Marketing Strategies In Increasing Product Sales (Study On Home Business Brown Sugar Tulus Bersih Desa Cahaya Negeri) - Cindy Silvia Putri Claudia; Kharul Bahrun (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the marketing strategy used by Brown Sugar (GM) home products